A review on endoscopic palliation of obstructive jaundice before surgery - Artifon, Everson L.A. (2017)
Since its development, endoscopic retrograde cholangiopancreatography (ERCP) has evolved from a simple diagnostic technique to an important therapeutic procedure. Obstructive jaundice is often the first and most common complication in patients with malignant disease of the extrahepatic biliary tract. Although preoperative biliary drainage (PBD) may be instituted in many centers, different studies have reported divergent results regarding its benefits in reducing the complications of hepatopancreatobiliary surgery, especially with regard to pancreatoduodenectomy for pancreatic cancer. In this review, we will summarize the current literature of PBD and describe its indications, possible benefits, and, when indicated, the appropriate interval before surgery.